Anisotropic atom-surface interactions in the Casimir-Polder regime - Taillandier-Loize, T. (2014)
The distance dependence of the anisotropic atom-wall interaction is studied. The central result is the 1/z 6 quadrupolar anisotropy decay in the retarded Casimir-Polder regime. Analysis of the transition region between nonretarded van der Waals regime (in 1/z 3 ) and Casimir-Polder regime shows that the anisotropy crossover occurs at very short distances from the surface, on the order of 0.03λ , where λ is the atom characteristic wavelength. Possible experimental verifications of this distance dependence using surface-induced inelastic transitions are discussed.